TRAINING OF MEDICAL STUDENTS IN TEACHING PSYCHIATRIC SCIENCES BASED ON SIMULATION TECHNOLOGIES (Eureka Journal of Health Sciences & Medical Innovation, 2026)
In our country, the use of registered patients during internship in the form of simulation for training in psychiatry is considered appropriate. This is the first study at our faculty using simulated psychiatry training. The purpose of this study is to propose a new method of teaching psychiatry to undergraduate students at the department and evaluate its feasibility and initial effectiveness. We chose depressive psychosis for modeling because this syndrome is common today and is found even among students.
Keywords: Depression, psychosis, psychiatry, simulation technology, medical institute, educational process.